Analisis Proksimat Pakan Ikan Nila Berbasis Tepung Udang Rebon dan Tepung Azolla - Renaldy Ruslan Manampa; Tusaban Tusaban; Dewi Shinta Achmad; Nur Jihan Fareranty Piu (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Feed quality determines the nutritional adequacy and economic efficiency of Nile tilapia culture, while dependence on conventional ingredients continues to increase production costs. This study evaluated the proximate composition of experimental feeds formulated with rebon shrimp meal (Acetes indicus) and Azolla meal as locally available animal- and plant-protein ingredients. A completely randomized design with four treatments and three replications was applied. The formulations consisted of P1 (75% rebon shrimp meal and 0% Azolla meal), P2 (50% and 25%), P3 (25% and 50%), and P4 (0% and 75%); each diet also contained 15% corn meal and 10% tapioca flour. Crude protein, moisture, ash, crude fat, and crude fiber were analyzed, followed by one-way analysis of variance and a 5% least significant difference test. Feed formulation significantly affected protein, moisture, ash, and fat, but not crude fiber. P1 produced the highest protein (18.20%) and ash (11.13%), whereas P2 produced the highest fat (5.80%) and the lowest moisture (1.49%). Crude fiber ranged from 2.97% to 3.65%. All treatments met the evaluated limits for moisture, ash, and crude fiber, and only P1 and P2 met the minimum fat criterion. However, no formulation reached the minimum 25% protein requirement for grow-out tilapia feed. Rebon shrimp meal and Azolla meal therefore have practical potential as local feed ingredients, but their proportions and processing must be optimized, particularly through protein enrichment, controlled Azolla pretreatment, and adjustment of energy-binding ingredients before biological feeding trials are conducted.